(untitled) (AYUSHDHARA, 2024)
Joint pain is a common complaint among the elderly. The 62 year-old male patient in this case study has osteoarthritis in his knee joint and has been enrolled in an Ayurvedic program for treatment. A type of Vatavyadhi called Janusandhigatavata is described in Ayurveda and is almost identical to osteoarthritis of the knee joint. In this case study, the impact of Janubasti combined with Mahanarayanataila and Dashmoolakwathnadi-swedana is evaluated. The patient has been advised to have two therapy sessions, each lasting six days, with a six-day break in between. According to the study, there has been a noticeable improvement in subjective parameters such as joint pain, Sandhi shoola, and pain during flexion and extension of the joint in Vatapurnadritisparsa, Prasaranakkunchanapravritisavedana. Following the study, Sandhi Shotha (joint swelling) is totally resolved.